2016
DOI: 10.1016/j.cub.2015.11.064
|View full text |Cite
|
Sign up to set email alerts
|

Motor Behavior Mediated by Continuously Generated Dopaminergic Neurons in the Zebrafish Hypothalamus Recovers after Cell Ablation

Abstract: Summary Postembryonic neurogenesis has been observed in several regions of the vertebrate brain, including the dentate gyrus and rostral migratory stream in mammals, and is required for normal behavior [1–3]. Recently the hypothalamus has also been shown to undergo continuous neurogenesis as a way to mediate energy balance [4–10]. As the hypothalamus regulates multiple functional outputs, it is likely that additional behaviors may be affected by postembryonic neurogenesis in this brain structure. Here, we have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
62
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(68 citation statements)
references
References 28 publications
(30 reference statements)
5
62
1
Order By: Relevance
“…In their hypothesis, TH1 expressing cells synthesize DA while TH2 expressing cells synthesize 5-HT in zebrafish. However, later studies do not support this idea (McPherson et al, 2016;Semenova, Chen, Zhao, Rauvala, & Panula, 2014). Based on our results revealing the presence of TH2 (but not necessarily TH1) in the DA 1 CFS-c cells in three vertebrate groups, it is more likely that TH2 is able to synthesize DA in this area.…”
Section: Da/5-ht Dual Phenotype Of the Hypothalamic Csf-c Cellsmentioning
(Expert classified)
“…In their hypothesis, TH1 expressing cells synthesize DA while TH2 expressing cells synthesize 5-HT in zebrafish. However, later studies do not support this idea (McPherson et al, 2016;Semenova, Chen, Zhao, Rauvala, & Panula, 2014). Based on our results revealing the presence of TH2 (but not necessarily TH1) in the DA 1 CFS-c cells in three vertebrate groups, it is more likely that TH2 is able to synthesize DA in this area.…”
Section: Da/5-ht Dual Phenotype Of the Hypothalamic Csf-c Cellsmentioning
(Expert classified)
“…Embryos were obtained from the following zebrafish lines: Tg(her4.3: EGFP) y83 (Yeo et al, 2007), Tg(ubi:loxP-eGFP-loxP-mCherry) cz1701 (Mosimann et al, 2011), Tg(−3her4.1:ERT2-Cre-ERT2) vu298 (Boniface et al, 2009;Mosimann et al, 2011), Et(Gal4-VP16,myl7:gfp) zc1066a , Tg(UAS-E1b:NTR-mCherry) jh17 (Davison et al, 2007;Pisharath et al, 2007), Tg(7xTCF-Xla.Siam:GFP) ia4 , Tg(hsp701:dkk1-GFP) w32 (Stoick-Cooper et al, 2007), Tg(hsp70l:wnt8a-GFP) w34 (Weidinger et al, 2005), lef1 zd11 , Tg(th2: GFP-aequorin) zd201 and Tg(th2:Gal-VP16) zd202 (McPherson et al, 2016). Embryos were staged according to Kimmel et al (1995).…”
Section: Zebrafishmentioning
confidence: 99%
“…In the previous studies, we analyzed the function of Wnt signaling on adult neurogenesis in the optic tectum of zebrafish (Shitasako et al, ), and Wnt‐related genes were expressed in the central nervous system of the zebrafish embryo (Clements, Ong, & Traver, ; Duncan, Panahi, Piotrowski, & Dorsky, ; Hashimoto et al, ; Untergasser, Martowicz, Hermann, Töchterle, & Meyer, ). Moreover, other studies also showed that Wnt signaling regulates self‐renewal and differentiation of neural stem cells in the physiological and regenerative conditions in the retina, hypothalamus, and spinal cord (McPherson et al, ; Ramachandran, Zhao, & Goldman, ; Strand et al, ). These studies suggest that Wnt signaling may play an important role not only in adult neurogenesis but also in regenerative neurogenesis.…”
Section: Introductionmentioning
confidence: 99%